Effect of age and cyclical heat stress on the serum biochemical profile of broiler chickens - João Paulo Rodrigues Bueno (Semina: Ciências Agrárias, 2017)
This study aimed to evaluate the influence of age and cyclical heat stress for 1 hour per day on the levels of serum proteins, metabolites, and enzymes in broiler chickens of 21-42 days of age. We used 420 male broiler chickens, Cobb Avian48 TM breed, in a completely randomized experimental design, composed of two treatments and six replicates. The treatments consisted of two thermal environments: one in which broiler chickens were raised under natural conditions of temperature and humidity for the first 42 days of age (control) and another in which chickens were subjected to heat stress at 36°C, from days 16 to 42, for 1 hour per day (1200-1300 hours). At 21, 28, 35, and 42 days of age, approximately 5 mL of blood was collected by cardiac puncture in two birds per replicate. In each serum sample, levels of total protein, albumin, globulin, albumin:globulin ratio, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and gamma-glutamyltransferase (GGT) activity and uric acid, creatinine, total cholesterol, triglycerides, high-density lipoproteins (HDL), very low density lipoproteins (VLDL), low-density lipoproteins (LDL), and glucose levels were determined. Concerning the environment and the age, no significant differences in the levels of glucose, uric acid, ALT, triglycerides, and very low density lipoproteins were observed. There was a significant interaction between the environment and the age for cholesterol and LDL values. At 21 days of age, cholesterol and LDL-cholesterol (LDL-C) were higher in birds under stress than in the control treatment birds, which did not occur in other age groups. Aspartate aminotransferase activity was higher in chickens under cyclical heat stress than in chickens subjected to control treatment and displayed a cubic response regarding the environment. The age of the birds influenced the values of total protein, albumin, globulin, albumin:globulin (A:G) ratio, creatinine, GGT, and HDL. In conclusion, cyclical heat stress, at 36ºC, for one hour, from days 16 to 42 of age increases serum AST, whereas cholesterol and LDL-C levels increase only at day 21, indicating that birds may have adapted to heat stress. Age influenced the activity of AST and GGT and levels of creatinine, total protein, albumin, globulin, A:G ratio, cholesterol, HDL-C, and LDL-C.